PRE-ESTABLISHED HARMONY: Studi Pemikiran Leibniz Dalam Perspektif al Quran - Padil, Moh. (ULUL ALBAB Jurnal Studi Islam, 2009)
Gotfried Wilhem Leibniz (1646-1716) is someone who concentrated his thought on the logical and metaphysical concept. Metaphysical concept believes that the concept of truth in the life of the nature is dominated by the definite balance. It is very interesting when Leibniz’s physical concept is discussed based on the Qur’anic teaching. According to the Qur’anic teaching, the God is alKhaliq, the creator of the universe and human. And the God descends His prophet to inform, to explain, to interpret and to give the directions to implement the Qur’an in the human's life. As long as human’s lives in the world follow the God’s way will reach the save ness and happiness. While according to Leibniz, the society who can not adopt to the cosmos’ rule will be destroyed. According to Qur'an, someone who does not follow the God’s will be destroyed, because the God's word is the guidance for human for reaching taqwa and merciful.